Answer:
0
Step-by-step explanation: 2x+8=2x+6 --> 8=6
8 cant be equal to 6 so this equation is wrong and has no solution.
Answer: 2 - 2*sin³(θ) - √1 -sin²(θ)
Step-by-step explanation: In the expression
cos(theta)*sin2(theta) − cos(theta)
sin (2θ) = 2 sin(θ)*cos(θ) ⇒ cos(θ)*2sin(θ)cos(θ) - cos(θ)
2cos²(θ)sin(θ) - cos(θ) if we use cos²(θ) = 1-sin²(θ)
2 [ (1 - sin²(θ))*sin(θ)] - cos(θ)
2 - 2sin²(θ)sin(θ) - cos(θ) ⇒ 2-2sin³(θ)-cos(θ) ; cos(θ) = √1 -sin²(θ)
2 - 2*sin³(θ) - √1 -sin²(θ)
The answer to the question is 752cm